Application of End User Computing Satisfaction Method to Analyze Customer Satisfaction in Using Mobile Application of National E-Commerce Travel Company - Damara Gugat, Rudy Max; Ozali, Imam; Saribanon, Euis (Jurnal Informasi dan Teknologi, 2023)
This study aims to ascertain perceived usefulness and service variables together with the degree of user satisfaction with the online travel agent application using the end-user computing satisfaction (EUCS) technique. Scholars employ a quantitative methodology. Questionnaires and literature reviews were the data collection techniques utilized to get the information required for this study. Respondents or clients who have downloaded or utilized the online travel agency application comprise the population used in this study. Purposive sampling is one of the sample techniques that the researcher utilized. One hundred individuals made up the sample. Microsoft Excel and the SmartPLS application version 3.3.9 are used for data processing. The measurement model, also known as the outer model, and the structural model, often known as the inner model, are the two models used in inferential data analysis using SmartPLS. According to the analysis's findings, user happiness is significantly impacted by and related to the content variable. User happiness is significantly impacted by and related to format variations. User satisfaction is significantly impacted by and related to the ease-of-use attribute. User happiness is influenced by and related to the perceived usefulness variable. User happiness is significantly impacted by and related to the service variable. In the meantime, user satisfaction is unaffected by the variables in this study that are rejected, specifically the accuracy variable, which is unrelated to user pleasure with the online travel agent application. User happiness is unaffected by the timing variable.